Commitment: a ‘contagious’ feeling between employees and customers in banking sector - Bilal Bourkha; Younes Belfellah; Victor Nasser Harkat (Geopolitics under Globalization)
This present paper tries to investigate relationship between dimensions of organizational commitment (OC) and brand commitment (BC) based on Allen and Meyer (1990) theory: affective, continuous and normative commitment. Population (443 people) of the present study included employees and customers from the same bank. Data collecting tool was two questionnaires, which were distributed among employees and customers. Data was analyzed with SEM to show the existing correlations. Results showed there is a moderated (0,424) relationship between OC and BC. Results confirm interpersonal exchange is a key concept in relationship management, in particular in services industry.